Determination of Growing Substances Standards in Preparation for Planting Seeds of Capers (Sapparis Spinosa L.) - Abdullaev, Zokir (American Journal of Biodiversity, 2025)
The article is written based on the results of experiments conducted to determine the optimal norms and times of working with seed-growing substances for the propagation of the Capersr (Capparis spinosa L.) plant by planting it from its seeds. In the article, to increase the fertility of plant seeds, IMK (indolyl butyric acid), IUK (indolyl acetic acid) and Retsuper growth agents (25, 50, 100 mg/l) were used for different periods of time (24, 48, 72 hours) the effect of saturated sowing on seed germination was determined, and the results of the research conducted in 2024-2025 are presented.